2015
DOI: 10.1088/0004-637x/812/1/83
|View full text |Cite
|
Sign up to set email alerts
|

MAGiiCAT V. ORIENTATION OF OUTFLOWS AND ACCRETION DETERMINE THE KINEMATICS AND COLUMN DENSITIES OF THE CIRCUMGALACTIC MEDIUM

Abstract: We investigate the dependence of gas kinematics and column densities in the Mg II-absorbing circumgalactic medium on galaxy color, azimuthal angle, and inclination to trace baryon cycle processes. Our sample of 30 foreground isolated galaxies at 0.3 < z gal < 1.0, imaged with the Hubble Space Telescope, are probed by background quasars within a projected distance of 20 < D < 110 kpc. From the high-resolution (∆v 6.6 km s −1 ) quasar spectra, we quantify the extent of the absorber velocity structure with pixel-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 53 publications
6
83
0
Order By: Relevance
“…In Paper I, we found a similar situation toward RCS2032727−132623. These cases strongly suggest that the scatter in W quasar 0 is not intrinsic to the CGM but rather dominated by the heterogeneous halo population, in which gas extent and smoothness is a function of host-galaxy intrinsic properties Chen et al 2010;Nielsen et al 2013bNielsen et al , 2015Rubin et al 2018c) and orientation (Nielsen et al 2015). It should therefore not be a surprise that quasar-galaxy samples exhibit more scatter than the present case.…”
Section: Direct Comparison With Quasar and Galaxy Surveysmentioning
confidence: 44%
“…In Paper I, we found a similar situation toward RCS2032727−132623. These cases strongly suggest that the scatter in W quasar 0 is not intrinsic to the CGM but rather dominated by the heterogeneous halo population, in which gas extent and smoothness is a function of host-galaxy intrinsic properties Chen et al 2010;Nielsen et al 2013bNielsen et al , 2015Rubin et al 2018c) and orientation (Nielsen et al 2015). It should therefore not be a surprise that quasar-galaxy samples exhibit more scatter than the present case.…”
Section: Direct Comparison With Quasar and Galaxy Surveysmentioning
confidence: 44%
“…For example, kinematic studies of some Lyα nebulae suggest rotational velocities and inflow rates consistent with those expected for these inspiraling streams (Martin et al 2014;Prescott et al 2015). Similarly, absorption line studies are beginning to emphasize the bimodal distribution of absorption detections, where detections along the galaxy's minor axis tend to show absorption properties consistent with outflowing gas, while detections roughly along the galaxy's major axis demonstrate properties (such as corotational inflow) that are consistent with inspiraling cold streams (Kacprzak et al 2010(Kacprzak et al , 2012a(Kacprzak et al , 2012bBouché et al 2012Bouché et al , 2013Crighton et al 2013;Nielsen et al 2015;Bouché et al 2016;Ho et al 2017).…”
Section: Discussionmentioning
confidence: 87%
“…There is even indication that local extended H I disks may be environmentally dependent on the galaxy's filamentary environment (Courtois et al 2015). At moderate redshift (z∼0.5-1.5), numerous absorption line studies of the circumgalactic medium of galaxies have begun to emphasize the bimodal properties of absorbers, where absorption along the galaxy's major axis tends to show high angular momentum (co-rotating) inflow, and absorption along the galaxy's minor axis shows observational signatures of outflow (Kacprzak et al 2010(Kacprzak et al , 2012a(Kacprzak et al , 2012bBouché et al 2012Bouché et al , 2013Crighton et al 2013;Nielsen et al 2015;Bouché et al 2016;Diamond-Stanic et al 2016;Ho et al 2017). At higher redshift (z∼2-3), kinematic studies of Lyα "blobs" have observed large-scale rotation consistent with high angular momentum cold gas accretion (Martin et al 2014;Prescott et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Cour-tois et al (2015) also indicated that local extended H I disks may be dependent on the galaxy's filamentary environment, suggesting there may be a fundamental distinction between the angular momentum content of filamentary accretion versus isotropic accretion. At moderate redshift (z ∼ 0.5-1.5) there are a growing number of absorption line studies of the circumgalactic medium of galaxies that have begun to emphasize the bi-modal properties of absorbers (Kacprzak et al, 2010(Kacprzak et al, , 2012aBouché et al, 2012Bouché et al, , 2013Crighton et al, 2013;Nielsen et al, 2015;Diamond-Stanic et al, 2016;Bouché et al, 2016;Bowen et al, 2016), where absorbers along a galaxy's major axis tends to show higher angular momentum inflows that are roughly corotating with the galactic disk and absorbers along a galaxy's minor axis tend to instead show observational signatures of outflowing gas. Increasingly, a number of absorption system observations seem to be in agreement with models that include massive, extended structures with inflowing disk-like kinematics (e.g., Bouché et al, 2016;Bowen et al, 2016) At higher redshift (z ∼ 2-3) kinematic studies of Lyα "blobs" have observed large scale rotation that seems consistent with high angular momentum cold gas accretion (Martin et al, 2014;Prescott et al, 2015), and there have also been recent detections of massive protogalactic gaseous disks that are kinematically linked to gas inflow along a cosmic filaments (Martin et al, , 2016.…”
Section: Observations Of High Angular Momentum Gasmentioning
confidence: 99%